Labor Market Equilibrium with Public Employment Agency - Christian Ludwig Holzner; Makoto Watanabe (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2015)
We develop and empirically test a labor market model with Public Employment Agencies (PEA) in order to understand why not all vacancies use the costless services provided by the PEA. We show that both the search market and the PEA can be active in equilibrium. In such an equilibrium, workers with a higher productivity have a higher chance of receiving a job offer and hence a higher value of searching privately. This enables firms in the search market to attract a better pool of applicants by posting a higher wage than firms registered with the PEA. Registered firms have no incentive to compete with firms in the search market since the application process in the PEA is coordinated so that the offered wage cannot affect the meeting probability. Using the German Job Vacancy Survey, we test the implications of our theory and find strong support for it.
Keywords: J63; J64; J68; 330